Educational applications of augmented reality: A bibliometric study. (July 2021) - Hincapie, Mauricio; Diaz, Christian; Valencia, Alejandro; Contero, Manuel; Güemes-Castorena, David
Highlights: We study the augmented reality educational applications and type of content. Few studies contrast the influence of the type of content on quantifiable variables. There is no preferred framework for the development of augmented reality content. 3D models have a better impact on memory and motivation than other content. Abstract: Augmented Reality (AR) has been used successfully in several industries; one of these is education. A systematic understanding of how AR contributes to education still lacks studies about the content type and its effects on learning outcomes. This article systematically analyzes the AR state-of-the-art in education, determines productivity and publication indicators in this field, and identifies research works that have studied how content type affects the learning outcomes. The methodology was performed through a bibliometric analysis using the Scopus database, focusing on AR's educational uses. Engineering education is the primary research trend, followed by simulation, tracking, and virtual reality . Education and e-learning also have leading roles within this analysis, along with gamification and human-computer interaction, whose impacts are further explored. There is no preferred design methodology for creating AR content. In its absence, most of the works suggest a design based on the developers' and researchers' experience. Graphical abstract: Image, graphical abstract